Proposing late transition metal complexes as frustrated Lewis pairs - a computational investigation - Pal, Amrita; Vanka, Kumar (Dalton Transactions, 2013)
There has been considerable interest in recent times to develop transition metal complex systems that can demonstrate metal-ligand cooperativity. It has recently been shown (Wass et al., J. Am. Chem. Soc., 2011, 133, 18463) that early transition metals can cooperate with ligands carrying phosphines as pendant groups, working as metal analogues to frustrated Lewis pairs (FLPs) to mediate in a variety of important reactions. What the current work attempts to do is to show how this concept of metal containing FLPs can be expanded to include late transition metal complexes as well: complexes that have been modified from existing systems that serve as efficient catalysts for homogeneous polymerization. A modified palladium complex has been considered in this regard as an example of a potential late transition metal FLP and studied with full quantum mechanical calculations. The calculations indicate that this complex would be effective at catalyzing ammonia borane dehydrogenation. The possibility of competing side reactions such as reductive elimination have also been considered, and it has been found that such processes would also yield stable products which could act as an FLP in catalyzing reactions such as the dehydrogenation of ammonia borane. The current work therefore expands the scope of metal containing FLPs to include late transition metals and demonstrates computationally the potential of such complexes for exhibiting metal-ligand cooperativity.